PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN JASA PENERBANGAN GARUDA INDONESIA AIRLINES (Studi kasus konsumen di Kota Palembang) - Zakaria Wahab; Marlina Widiyanti (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2014)
The purpose of this research are to find out the influence of service quality which is consisting of proof dimension in physique, reability, responsiveness, guarantee, and empathy to consumer satisfaction in using Garuda Indonesia service flight in City of Palembang either partially or simultaneously. The amount of samples in this research are 105 Garuda Indonesia passangers flight from Palembang-Jakarta or vice-versa. The population in this research are society domicile in Palembang City. The formulation of the problem in this research is how the influence of service quality seen from tangibles, reliability, responsiveness, assurance and emptahy to the the Satisfaction of Consumers of Flight PT. Garuda Indonesia Airlines in Palembang city. The hypothes is of this research is service quality has significant influence to the satisfactionof airlines service consumers PT. Garuda Indonesia Airlines. The theory used in this research is Marketing Management Theory related to the service quality. It uses descriptive quantitative and case study using survey. This is also explanatory. Utilized Sampling Technique are non probability sampling. Utilized technique analysis are multiple regression analysis. The research result indicate that percentage of the reliability, responsiveness and guarantee dimension has positive and significant influence to consumer satisfaction are 44,4%.Key word: Tangibles, Reliability, responsiveness, Assurance, Empathy and Satisfaction of consumer